Growth and survival of the oyster Crassostrea brasiliana (Lamarck, 1819) kept inside a shrimp’s culture pond - da Rosa, Leonardo Cruz (Arquivos de Ciências do Mar, 2014)
The present study evaluated the growth and survival of the oyster Crassostrea brasiliana kept in a shrimp farm in order to evaluate the possibility of its being used as a biofilter directly in culture ponds. Four bags containing 100 oysters with an average height of 40.8 ± 8.7 mm were installed inside the shrimp pond and after 4 months, reached an average height of 50.3 ± 8.7 mm, resulting in an increased monthly rate of 2.37 mm/month. The final survival rate was 67%. Despite the slow growth, the high observed survival rate suggests that it is viable to cultivate oysters directly in shrimp ponds. However, the effectiveness of removing nutrients and particles should be tested.